Effects of Salary Standardization Law on the Socio-Economic Status, Work Performance, Motivation and Job Satisfaction of Teachers - Ofelia A Bajarin; Rosanna D Gonzales (ASEAN Multidisciplinary Research Journal, 2019)
This study aimed to describe the effects of salary standardization law on the socio-economic status, work performance, motivation and job satisfaction of teachers. It covered 405 public school teachers in the country regardless of their point of origin. It made used of descriptive-evaluative design. Moreover, a survey questionnaire was used and was processed using descriptive and inferential statistics.Majority of the teachers were young and in the early adulthood, with master’s units,and with at least one organizational affiliation, earning salary grade 13, and were still young in the service. They earn low monthly net income, have at least one other source of income, and performing very satisfactory. Teachers have small number of family members and dependents, were living in rural areas and were spending monthly expenses at an average. They have three to six assets which majority, are electronic gadgets, motorcycles and appliances, majority also engaged in loans which were salary, emergency and multipurpose loans.In terms of the perceived effects of SSL on the socio-economic status of teachers, it garnered a grand weighted mean of 3.11 and descriptively rated as “moderate”. On spending habits and borrowing practices it garnered an average mean of 3.12 and 3.14 which both descriptively rated as “moderate” respectively. Furthermore, salary standardization law has “high” effects along the teachers’ work performance (weighted mean of 3.79), motivation (weighted mean of 3.69), and job satisfaction (weighted mean of 3.66).The overall level of socio economic status, work performance, motivational level, and job satisfaction of teachers does not differ in general.In addition, net income registered a highly significant relationship (r=+.564, p=.000) to their salary grade. It implies that teachers who have higher salary grade and receiving higher salary tend to have bigger net income.